2020
DOI: 10.1098/rspb.2019.2578
|View full text |Cite
|
Sign up to set email alerts
|

Mate selection based on labile traits affects short-term fitness in a long-lived seabird

Abstract: In long-lived monogamous social species, partner compatibility can play a crucial role in reproductive success. We evaluated assortative mating based on body condition (plasma triglyceride concentration), diet (δ 15 N), and foraging habitat (δ 13 C) in the blue-footed booby Sula nebouxii, a long-lived monogamous seabird. We investigated the effects of assortative mating (sum of triglycerides in a pair) and asymmetry within pairs (residuals from regression of female-male triglycerides) on reproductive performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 69 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Plasma metabolites are commonly used as indicators of individual quality, a term that is linked to long-term heterogeneity between individuals (Wilson and Nussey 2010 ). Previous studies in Blue-footed Boobies confirmed a relationship between female triglyceride concentrations (sampled during courtship) and the summed triglycerides of a pair to their reproductive performance (González-Medina et al 2018 ; 2020 ). González-Medina et al ( 2020 ) also found a correlation between the summed triglycerides of a pair measured during courtship and those measured during chick-rearing.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Plasma metabolites are commonly used as indicators of individual quality, a term that is linked to long-term heterogeneity between individuals (Wilson and Nussey 2010 ). Previous studies in Blue-footed Boobies confirmed a relationship between female triglyceride concentrations (sampled during courtship) and the summed triglycerides of a pair to their reproductive performance (González-Medina et al 2018 ; 2020 ). González-Medina et al ( 2020 ) also found a correlation between the summed triglycerides of a pair measured during courtship and those measured during chick-rearing.…”
Section: Discussionmentioning
confidence: 75%
“…In a related species, the Australasian gannet ( Morus serrator ), each sex targeted prey that differs in nutrient content (Machovsky-Capuska et al 2016 ). However, previous studies found no dietary segregation between the sexes in Blue-footed boobies (González-Medina et al 2017 , 2020 ). Nevertheless, it is possible that females have a higher assimilation rate during the pre-laying period and are freer to forage than males due to their differential breeding roles, thus foraging at specific areas and prey species to satisfy their nutritional needs.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations